ChIP-Seq data analysis: identification of protein-DNA binding sites with SISSRs peak-finder - Narlikar, Leelavati; Jothi, Raja (Methods in molecular biology, 2012)
Protein-DNA interactions play key roles in determining gene-expression programs during cellular development and differentiation. Chromatin immunoprecipitation (ChIP) is the most widely used assay for probing such interactions. With recent advances in sequencing technology, ChIP-Seq, an approach that combines ChIP and next-generation parallel sequencing is fast becoming the method of choice for mapping protein-DNA interactions on a genome-wide scale. Here, we briefly review the ChIP-Seq approach for mapping protein-DNA interactions and describe the use of the SISSRs peak-finder, a software tool for precise identification of protein-DNA binding sites from sequencing data generated using ChIP-Seq.

Clare: cracking the language of regulatory elements - Taher, Leila; Narlikar, Leelavati; Ovcharenko, Ivan (Bioinformatics, 2012)
CLARE is a computational method designed to reveal sequence encryption of tissue- specific regulatory elements. Starting with a set of regulatory elements known to be active in a particular tissue/process, it learns the sequence code of the input set and builds a predictive model from features specific to those elements. The resulting model can then be applied to user-supplied genomic regions to identify novel candidate regulatory elements. CLARE's model also provides a detailed analysis of transcription factors that most likely bind to the elements, making it an invaluable tool for understanding mechanisms of tissue- specific gene regulation.